INFORMATION SUPPORT OF DISTANCE LEARNING COURSE "THEORY OF INVENTIVE PROBLEM SOLVING" - Solodovnik, A.O.; Sharko, В.Д. (Journal of Information Technologies in Education (ITE), 2011)
This article describes experience of developing a distance course «Theory of inventive problem solving» based on distance learning system «Kherson Virtual University» aimed at students of 4 course of specialty «PMSE. Physics».